The relationship between two species of fur seals Arctocephalus Tropicalis (Gray) and A. Gazella (Peters) on Marion Island - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Dissertation (MSc (Zoology))--University of Pretoria, 1984.